Significance of a sustainable business model : the case of IKEA, swedish retailer in furniture and home accessories - Shahid, Hira (SLU/Dept. of Economics, 2020)
In the modern era of industrialization resource depletion and carbon footprint of commercial activities is an important concern. Awareness about the impact of conventional commercial activities is increasing among the consumers as well as organizations. As the demand of goods may well continue to increase with a consistent increase in population, responsible organizations have been looking for ways to conduct their activities in a more sustainable manner and rational customers tend to prefer Sustainable Products (SP). The dilemma, however, is how to evolve conventional businesses into such a state that continues to fulfil the expectations of the customers while minimizing the impact on environment. The focus of this study is to understand why conventional Business Models (BM) should be transformed into Sustainable Business Models (SBM) and how can it help to meet the interests of customers. The aim of this thesis is to understand a link between SBM in producing SP. This research intends to understand the importance of customer in light of Stakeholder Theory (ST) and importance of Circular Economy (CE) to achieve a SBM. Furthermore, the author of this study derived a conceptual framework from theories to answer the research question. To investigate this scenario a qualitative approach based on secondary data, a case study of IKEA was conducted. The study has also considered insights from previous researches on IKEA regarding sustainability issues. Pattern matching technique was applied to analyse theoretical and empirical data. The empirical study supported the theoretical framework and revealed a matching pattern. This pattern match supported the selection of theoretical framework. Based on this analysis, it could be argued that CE principles and strong Corporate Governance (CG) can possibly help businesses to strengthen their business strategy as well as help transform their BM into a SBM. However, considering the complex supply chain and dependencies of large businesses on the legal, economic, social and industrial environment they operate in, there is a lot yet to be done to get to the ideal stage of having a fully SBM.